Biochemical parameters and dietary adherence in type 2 diabetics on hemodialysis (European Journal of Health Research, 2024)
Introduction: Non-adherence to diet and fluid intake of the patient on hemodialysis can lead to the accumulation of toxic metabolites in the blood, resulting in increased morbidity and premature death. Objective: to determine biochemical parameters and diet adherence in patients with type 2 diabetes on hemodialysis attending the dialysis unit of the General Hospital IESS Riobamba.  Methods: A quantitative correlational, prospective, quasi-experimental, longitudinal design study was carried out in 87 subjects with diabetic nephropathy of both sexes between 40 and 70 years of age, who were receiving dialysis treatment. Biochemical measurements were taken (hematological, metabolic and lipid profile, albumin and electrolytes) and the questionnaire of non-adherence to diet and fluids for hemodialysis (DDFQ) was applied. Results: Significant differences were found (p
Keywords: diet; liquids; hemodialysis; type 2 diabetes; electrolytes